2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20170454
|View full text |Cite
|
Sign up to set email alerts
|

A clinicoepidemiological study of cutaneous tuberculosis in a tertiary care teaching hospital in Andhra Pradesh, India

Abstract: <p class="abstract"><strong>Background:</strong> Cutaneous tuberculosis constitutes 1.5% of extra pulmonary tuberculosis and the disease continues to be a challenging one because of its multifaceted presentation. The present study was done to document the most common type of cutaneous tuberculosis, atypical presentations if any and response to directly observed therapy short course (DOTS)<span lang="EN-IN">.</span></p><p class="abstract"><strong>Methods:</stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…6,9,13 The most common type of cutaneous tuberculosis in our study was lupus vulgaris (35%) which was similar to some studies. 10 However few other Indian studies found tuberculosis verucca cutis. 11 as most common type and few others found scrofuloderma as the most common type.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6,9,13 The most common type of cutaneous tuberculosis in our study was lupus vulgaris (35%) which was similar to some studies. 10 However few other Indian studies found tuberculosis verucca cutis. 11 as most common type and few others found scrofuloderma as the most common type.…”
Section: Discussionmentioning
confidence: 97%
“…9 Our study is a keen effort to find out the incidence, clinical profile, and histopathological features of cutaneous tuberculosis atypical presentations if any and response to directly observed short course (DOTS) therapy. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] In India, most of the studies on cutaneous TB have reported males being more commonly affected than females. [ 5 12 13 14 ] Maximum number of our cases belonged to the second and third decades. This result was consistent with studies conducted by Thakur BK et al .,[ 12 ] Aruna C et al .,[ 13 ] Punia RS et al .,[ 14 ] and Shivanna R et al .…”
Section: Discussionmentioning
confidence: 99%
“…The main etiological agent of the Cutaneous tuberculosis is Mycobacterium tuberculosis —occasionally M. bovis or BCG vaccine (an attenuated strain of M. bovis ) [ 12 , 13 ].…”
Section: Etiological Agentmentioning
confidence: 99%
“…Lupus vulgaris is the most common form of cutaneous tuberculosis in Europe, India, and Nepal [ 8 , 13 , 16 ]. It is a chronic, progressive, paucibacillary form of cutaneous tuberculosis which occurs primarily in the previously sensitized individual [ 23 , 24 ].…”
Section: Endogenous Tuberculosismentioning
confidence: 99%